A rare case of leiomyosarcoma arising from vault post-hysterectomy - Bhuyar, Sonal; Sontakke, Bhavana; Dharmale, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Fibroid/Leiomyoma is the most common benign tumor of the uterus, arising from uterine smooth muscle. Atypical leiomyomas are rare forms of Myoma (fibroid uterus), of which recurrent atypical leiomyoma post hysterectomy is rarer and its converting in leiomyosarcoma arising from vault is rarest. Here we report an unusual case of a 76yrs female, with leiomyosarcoma in an atypical leiomyoma arising from vault post-hysterectomy. A 76-year-old P3L3 patient presented with pain and distension of abdomen, post hysterectomy done 4 years back for chronic inversion and cervical fibroid polyp she was diagnosed as atypical leiomyoma. Laparotomy was done with a provisional diagnosis of leiomyosarcoma. Though Rarest (0.13-0.26%), a differential diagnosis of neoplastic changes should be kept in mind in patients with atypical leiomyoma, in patients presenting with any mass/pain abdomen, irrespective of any gynaecological complaints. This case shows that though it is unexpected after hysterectomy, leiomyosarcoma has to be considered in a case of abdominal mass. Atypical leiomyoma develops approximately in one to five cases out of 1,000 women with fibroid and it getting converted in leiomyosarcoma is rarest. Hence, diagnosis of leiomyosarcoma should always be kept in mind though the patient is hysterectomised.